Assessment of Dental Implant Site Dimensions And Alveolar Bone Density in The Mandible Using Cone Beam Computed Tomography - Karim, Omran K.; Fatah, Ahlam A. (Journal of Baghdad College of Dentistry, 2018)
Background: The quantity and the quality of available bone, influence the clinical success of dental implants surgery. Cone beam Computed tomography is an established method for acquiring bone images before performing dental implant. Cone beam computed tomography is an essential tool for treatment planning and post-surgical procedure monitoring, by providing highly accurate 3-D images of the patient's anatomy from a single, low-radiation scan which yields high resolution images with favorable accuracy. The aim of study is the Measurement of alveolar bone (height and buccolingual width) and density in the mandible among Iraqi adult subject using CBCT for assessment of dental implant site dimensions.Material and method: The study sample include (60) Iraqi subjects (30 male and 30 females) aged between 20-65 years, sagittal view of Cone beam computed tomography was obtained to measure the height ,width and alveolar bone density of the mandibular anterior area, while coronal view was used to measure the height ,width and alveolar bone density assessment of the mandibular premolar and molar areas. Measurement of mandibular bony height and width was in(mm)and each of the three mandibular areas were represented by seven consecutive measurements for bony height and width and these seven stations were set using an average distance of 2 mm apart while the bone density in Hounsfield unit (HU) with point of measurement represent the mean of density to the area located between the height and buccolingual width.Results:The Statistical analysis of linear measurements of mandibular bone which include the bony height , width and density showed that the mean values of all three measurements are significantly higher in males than females also there was statistically significant difference in the mean bone density of mandibular areas which was highest in anterior area and lowest in the molar area followed by premolar area among both gender, mandibular bony height showed a statistically insignificant very weak negative linear correlation with age in all the three examined mandibular areas while the effect of age on bucolingual width was significantly higher among subjects older than 50 years compared to those younger than 50 years old.Conclusion: The mean bony height was highest in anterior area and lowest in premolar area followed by molar area, while the mean bony width was lowest in anterior area and highest in molar area followed by premolar area , finally the mean bone density was highest in anterior area and lowest in molar area followed by premolar area.